A RARE CASE OF COMBINED UTERINE RUPTURE: RUPTURE OF THE UTERUS FROM THE VAULT COMBINED WITH A CERVICAL RUPTURE EXTENDING TO THE LOWER UTERINE SEGMENT - Цхай, Виталий Борисович; Домрачева, Марина Яковлевна (Mother and Baby in Kuzbass, 2024)
Among all types of maternal birth traumatism, uterine rupture is the most formidable and deadly complication. In recent years, due to the increasing frequency of cesarean sections, histopathic ruptures associated with uterine scar failure have become the leading cause of uterine rupture. In modern obstetrics, uterine rupture from the vaginal vaults is extremely rare, and therefore there are no clear recommendations for physicians on surgical tactics in this situation.